Identification, function validation and haplotype analysis of salt-tolerant genes of lectin receptor kinase gene family in sorghum (Sorghum bicolor L.) - Li Mao; Li Mao; He Huazhuan; He Huazhuan; Gao Haiyan; Gao Haiyan; Huang Wangqi; Cai Qizhe; Cai Qizhe; Yan Guiyun; Yan Guiyun; Cheng Qingjun; et al. (Frontiers in Genetics, 2024)
IntroductionSalt stress is one of the significant challenges in sorghum production, greatly impacting the yield of S. bicolor. L-type lectin receptor kinases (LLRKs) are essential for plant stress tolerance, yet a comprehensive genome-level analysis in this species has not been conducted.Materials and methodsMembers of the SbLLRLK gene family were identified using bioinformatics methods. Gene structures, motifs, and phylogenetic relationships were analyzed. Subsequently, expression profiles under various stress conditions were examined using transcriptome data. Furthermore, functional validation was performed through homologous gene alignment and transgenic analysis, focusing on the gene SORBI_3004G304700.ResultsThis study identified 49 SbLLRLK genes in Sorghum bicolor, categorized into four groups based on their lectin domain characteristics. Expression analyses revealed diverse patterns under salt, drought, and heat stresses. SORBI_3004G304700 was identified as a negative regulator of salt stress tolerance, with three unique haplotypes identified through haplotype analysis, suggesting a role in salt stress adaptation. Haplotype analysis of SORBI_3004G304700 revealed three unique haplotypes, with haplotype1 being the most prevalent, possibly due to selective advantages for salt stress tolerance.DiscussionThese findings offer valuable insights into the biological research on the role of the LLRLK gene family in Sorghum bicolor’s response to salt stress. The functional characterization of SORBI_3004G304700 and the identification of haplotypes associated with salt tolerance provide valuable insights for molecular breeding and genetic enhancement of sorghum.